Impact of COVID-19 Restrictions on Western Australian Children’s Physical Activity and Screen Time - Nathan, Andrea (Int J Environ Res Public Health, 2021)
Physical activity is essential for children’s healthy development, yet COVID-19 physical distancing restrictions such as school closures and staying at home, playground closures, and the cancelling of organised community sport have dramatically altered children’s opportunities to be physically active. This study describes changes in levels of physical activity and screen time from February 2020 (i.e., before COVID-19 restrictions were introduced in Western Australia) to May 2020 (i.e., when COVID-19 restrictions were in place). Parents of children aged 5 to 9 years from Western Australia were eligible to participate and recruited through convenience sampling. An online survey instrument that included validated measures of their children’s physical activity (unstructured, organized, home-based, indoor/outdoor active play, dog play/walking), sociodemographic, and other potential confounders was administered to parents. Paired t-tests and mixed ANOVA models assessed changes in physical activity outcomes. The analytic sample comprised parents of 157 children who were 6.9 years of age (SD = 1.7) on average. Overall, weekly minutes of total physical activity (PA) did not change from before to during COVID-19. However, frequency and duration (total and home-based) of unstructured physical activity significantly increased. Outdoor play in the yard or street around the house, outdoor play in the park or playground or outdoor recreation area, and active indoor play at home all significantly increased. Frequency and total duration of organised physical activity significantly declined during COVID-19 distancing. During Western Australian COVID-19 restrictions, there was an increase in young children’s unstructured physical activity and outdoor play and a decrease in organised physical activity. It remains to be seen whether children’s increased physical activity has been sustained with the easing of physical distancing restrictions.